Jawabanmu

2014-08-19T20:21:40+07:00

2x + y = 5
3x - 2y = 4

Mengeliminasi x                       Mengeliminasi y

(3).2x + (3).y = (3).5                 (2).2x + (2).y = (2).5
(2).3x + (2).-2y = (2).4              (1).3x + (1).-2y = (1).4

6x + 3y = 15                              4x + 2y = 10
6x - 4y = 8                                 3x - 2y = 4
---------------------- -                     ------------------ +
7y = 7                                        7x = 14
y = 1                                           x = 2

Pembuktian

2x + y = 5               3x - 2y = 4
2.(2) + (1) = 5         3.(2) - 2(1) = 4
4 + 1 = 5                  6 - 2 = 4
5 = 5                         4 = 4

2014-08-19T20:30:05+07:00
2x+y=5   x  2 = 4x+2y=10
3x-2y=4  x  1 = 3x-2y  =4
                      7x        =14
                     x = 14 :7
                     x = 2
2x+y=5
2(2)+y=5
4+y=5
y=5-4
y=1


jadi x = 2
      y = 1